2021
DOI: 10.1038/s41598-021-03456-9
|View full text |Cite
|
Sign up to set email alerts
|

Salivary gland dysfunction and salivary redox imbalance in patients with Alzheimer’s disease

Abstract: Alzheimer’s disease (AD) is associated with the deposition of β-amyloid in the brain. AD accounts for over 50% of cases of dementia which results from disturbances in redox homeostasis. Indeed, increased intensity of protein oxidation and nitration as well as lipid peroxidation is observed in brain areas with considerable amounts of amyloid plaques and neurofibrillary tangles. However, little is known about the oxidoreductive balance of salivary glands in AD patients. Therefore, the aim of this study was to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 51 publications
2
21
0
Order By: Relevance
“…However, other studies of serum proteins found that the serum YKL-40 was the only protein (of Aβ42/Aβ40, YKL-40, and t-tau) that was still higher in vascular dementia patients even after 4 weeks of hospital treatment, suggesting the usefulness of YKL-40 for vascular dementia diagnostics [39]. These dementia markers are also immune-related proteins and co-occur with oxidative stress damage, even in saliva [40]. Another study found higher d-serine levels in the serum and cerebrospinal fluid (CSF) of persons suffering from AD [41].…”
Section: Other Immune-related Markersmentioning
confidence: 93%
“…However, other studies of serum proteins found that the serum YKL-40 was the only protein (of Aβ42/Aβ40, YKL-40, and t-tau) that was still higher in vascular dementia patients even after 4 weeks of hospital treatment, suggesting the usefulness of YKL-40 for vascular dementia diagnostics [39]. These dementia markers are also immune-related proteins and co-occur with oxidative stress damage, even in saliva [40]. Another study found higher d-serine levels in the serum and cerebrospinal fluid (CSF) of persons suffering from AD [41].…”
Section: Other Immune-related Markersmentioning
confidence: 93%
“…Increased deposition of protein glycoxidation products was found in the brains of patients with Alzheimer’s disease and Parkinson’s disease. 8 , 38 , 67 , 71–74 Thus, further studies are needed on the use of saliva to evaluate the aging of the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous scientific publications indicate that AD patients have systemic manifestations accompanying nervous system dysfunction, which suggests that the disease affects both the brain and peripheral organs, including the salivary glands [ 8 , 9 , 10 , 39 ]. Salivary gland dysfunction in AD patients was associated with salivary redox imbalance linked with chronic inflammation [ 10 ]. Recently, it has been described as a hypothetical mechanism for LPS-induced downregulation of AQP5 [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies indicates that patients with AD have systemic manifestations accompanying nervous system dysfunction, which suggests that the disease affects both the brain and the peripheral organs. Several studies have reported changes in the function and morphology of salivary glands in AD [ 7 , 8 , 9 , 10 ]. Saliva is a biofluid produced mainly by three pairs of major salivary glands, the submandibular, parotid, and sublingual glands [ 11 ].…”
Section: Introductionmentioning
confidence: 99%